2009
DOI: 10.1017/s1041610209990949
|View full text |Cite
|
Sign up to set email alerts
|

Why suicide? Elderly people who committed suicide and their experience of life in the period before their death

Abstract: The results lead us to argue that their suicides should be considered as existential choices. The sum total of the different forms of strain had made life a burden they could no longer bear. Age meant that they were in a phase of life that entailed closeness to death, which they could also see as a relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 16 publications
6
85
0
4
Order By: Relevance
“…Anxiety is also mentioned on a disorder level in several of the studies [10, 12, 13], but anxiety symptoms in depressed patients have not been studied in relation to suicide among older patients. In contrast, there are several studies that report no association between suicidal ideation or suicides committed and psychiatric disorders in older adults [10, 14, 15]. Altogether, whether anxiety symptoms in depressed patients could be associated with suicidality among older adults or vice versa remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety is also mentioned on a disorder level in several of the studies [10, 12, 13], but anxiety symptoms in depressed patients have not been studied in relation to suicide among older patients. In contrast, there are several studies that report no association between suicidal ideation or suicides committed and psychiatric disorders in older adults [10, 14, 15]. Altogether, whether anxiety symptoms in depressed patients could be associated with suicidality among older adults or vice versa remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Få informanter hadde sett tegn på alvorlig psykisk lidelse (11), og mange uttrykte eksplisitt at avdøde ikke hadde vaert deprimert (11,13). Dette står i sterk kontrast til det som er konklusjonen i de fleste kvantitative PA-studier, nemlig at nesten alle som har tatt sitt liv, ble funnet å ha én eller flere psykiske lidelser (3), med tilhørende kausale implikasjoner.…”
Section: Som Man Spør Får Man Svar?unclassified
“…Previous research in the Norwegian context demonstrated that elderly individuals who attempted suicide perceived that everything that had given value to their lives had been lost, life was increasingly experienced as a burden, and their perception of themselves was "losing oneself" [40]. Holm and Severinsson [14] revealed one main theme: "a struggle to perceive meaning in the meaningless".…”
Section: Discussionmentioning
confidence: 99%